ChemInform Abstract: Development of an Improved Rhodium Catalyst for Z‐Selective anti‐Markovnikov Addition of Carboxylic Acids to Terminal Alkynes. Issue 4 (28th January 2014) - Wei, Siping; Pedroni, Julia; Meissner, Antje; Lumbroso, Alexandre; Drexler, Hans‐Joachim; Heller, Detlef; Breit, Bernhard
Abstract The regioselective Rh‐catalyzed addition reaction of carboxylic acids to terminal alkynes in the presence of 2‐diphenylphosphinomethylpyridine as the catalytic ligand is studied.